2005
DOI: 10.1007/s10705-005-0408-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different Mg fertilizer sources on the magnesium availability in soils

Abstract: Pot experiments with different soils were conducted to determine the effect of different Mg fertilizer sources on magnesium availability. The sources studied included Kieserite ͑MgSO 4 H 2 O͒, a synthetic magnesium sulphate ͑SMS͒ with variable content of crystal water and a calcined magnesite ͑Mg-oxide͒. The three magnesium fertilizers vary greatly in their solubility in water, affecting the availability to plants once applied to the soil. Whereas Kieserite dissolved gradually and SMS immediately, Mg-oxide rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 2 publications
1
7
0
1
Order By: Relevance
“…A pot study of Osemwota et al (2007) with soils from southern Nigeria showed significantly greater uptake of Mg by maize for a soil with Ca:Mg ratio of 1 compared to 8; this result did not hold in field experiments and did not relate to differences in productivity. A pot experiment by Härdter et al (2004) illustrated a fourfold decrease in responses of maize production to NPK fertilizer when the Ca:Mg balance was raised from 1 to 10. Besides this, it is well known that crop demand for Mg changes largely under adverse conditions, and hence that the cation plays a prominent role in strengthening the tolerance of crops to various stresses ( Gransee and Führs, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…A pot study of Osemwota et al (2007) with soils from southern Nigeria showed significantly greater uptake of Mg by maize for a soil with Ca:Mg ratio of 1 compared to 8; this result did not hold in field experiments and did not relate to differences in productivity. A pot experiment by Härdter et al (2004) illustrated a fourfold decrease in responses of maize production to NPK fertilizer when the Ca:Mg balance was raised from 1 to 10. Besides this, it is well known that crop demand for Mg changes largely under adverse conditions, and hence that the cation plays a prominent role in strengthening the tolerance of crops to various stresses ( Gransee and Führs, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although exchangeable-Mg levels were the primary factors determining yield increases (Supplementary Tables S1 and S2), there were clear interactions between soil pH and fertilizer types ( Supplementary Table S3). Mg fertilizers are generally classified into rapidly released (Mg-R) and slowly released (Mg-S) types with distinct particle size and water solubility (Mayland and Wilkinson, 1989;Härdter et al, 2004;Loganathan et al, 2005). Mg-S releases slowly and improved yield more efficiently as compared to Mg-R ( Figure 8C).…”
Section: Soil Conditions Primarily Determine Yield Effects Of Mg Fertmentioning
confidence: 99%
“…The nutrient release characteristics from a Mg fertilizer source are important for the sustained supply of Mg to plants. Very slowly releasing sources may lead to a temporal undersupply, and very rapidly releasing sources may be prone to dramatic Mg losses by leaching . Moreover, Mg and Ca appear to have an antagonistic relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Very slowly releasing sources may lead to a temporal undersupply, and very rapidly releasing sources may be prone to dramatic Mg losses by leaching. 43 Moreover, Mg and Ca appear to have an antagonistic relationship. 44 Excessive Ca in soil leads to Mg deficiency, which may result in nutrient imbalances, depress Mg uptake by crop root, and in turn its translocation to plant parts and finally affect yields of crop.…”
Section: Effects Of Mg Application On Total Mg Accumulation Amounts Imentioning
confidence: 99%